The influence of leg muscle power, waist flexibility and self-confidence on soccer long passing ability - Mardepi Saputra; Arsil Arsil; Ardo Okilanda; Mario Febrian; Riand Resmana; Andre Igoresky; Yovhandra Ockta; Rifqi Festiawan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The problem in this study is the low ability of Long Passing soccer school players Buah Hati. This study aims to see the effect of leg muscle strength, waist flexibility and self-confidence on long passing ability, both directly and indirectly and simultaneously. This type of research is quantitative with a path analysis approach. the sample in this study were all 30 players of Buah Hati Football School. Sample withdrawal using saturated sampling technique. The leg muscle power instrument uses the Vetical Jump Test, waist flexibility using the Sit and reach test, confidence using a Likert scale model questionnaire and long passing ability with the Aerial Pass for Accuaracy test. The results showed that, (1) there is a direct effect of leg muscle power on long passing ability with ρz1 = 0.337 or 11.35%, (2) there is a direct effect of waist flexibility on long passing ability, with ρz2 = 0.458 or 20.97%, (3) there is a direct effect of self-confidence on long passing ability, with ρz3 = 0.225 or 5.06%, (4) there is an indirect effect of leg muscle power on Long Passing ability through self-confidence, with ρz31 = 0.1131 or 11.31%, (5) there is an indirect effect of waist flexibility on Long Passing ability through self-confidence, with ρz32 = 0.0893 or 8.93% and (6) there is an effect of leg muscle power, waist flexibility and self-confidence simultaneously on three point shooting ability, with ρz123 = 0.942 or 94.2%.